(untitled) (The International Journal for Scientific Research, 2024)
Islam and the Arabic language entered Senegal thanks to the tremendous efforts made by Muslim scholars in the field of Islamic advocacy. Among these noble efforts are what is due to the Almoravid reform movement led by Abdullah bin Yassin in the eleventh century AD, and some are due to the efforts of Arab Muslim merchants whose tours were commercial and preaching, and which began in countries such as Libya, Tunisia, and Algeria. Likewise, the conversion of one of the kings of Senegal to Islam in the year 1040 AD was a major reason for the spread of Islam, as he approved the law of Islam in his subjects after his conversion to Islam, and spent a lot of money to teach his people the Islamic religion, and opened diplomatic relations between his state and some Arab countries, and then came the era of sheikhs and Sufi orders. , which was distinguished from a religious, moral, and cultural standpoint, and they had a very great impact in spreading Islam and the Arabic language in Senegal. Among these virtuous sheikhs: Sheikh Ibrahim Nias, whose effective contributions to spreading Islam and the Arabic language we will highlight in this research. The Sheikh had a great struggle in this field despite the French’s fight against him. He wrote many books in various Islamic fields and opened many schools. A group of Senegalese scholars studied under him. He formulated many of these sciences in the form of poetic verses that the students memorized after they had memorized the Book of God Almighty. In this research, we will learn about the Sheikh and his efforts in the Arabic language and Islamic sciences based on his interpretation entitled “In the Riyadh of Interpretation of the Holy Qur’an.” The research includes an introduction in which a definition of Islam in Senegal is mentioned. The first section includes a brief introduction to the Sheikh’s life, and the second section includes an introduction to his scientific and practical efforts, and his approach to interpreting the Holy Qur’an through his six-volume book, then a conclusion that includes the most important results.